TEACHING OF PHYSICS FOR STUDENTS OF NATURAL DIRECTION WITH INNOVATION TECHNOLOGIES - Farmonov, Utkir (Физико-технологического образование, 2020)
The article deals with the methodology of teaching physical science in the field of natural science (mathematics). In the field of natural science education the necessary theoretical methods for the use of new pedagogical technologies in teaching physics and, consequently, the formation of students' scientific thinking and world outlook are provided